Island health review, progress and the way forward in the Western Pacific Region - Thant Zin; Than Myint; Kyaw Htay; Shamsul B. S (Malaysian Public Health Physicians Association, 2014)
Island health differs from other health care systems, particularly in that there are limited resources and referral faculties available. With globalisation and climate change, island populations have become increasingly vulnerable to natural disasters and global pandemics. This study will identify, explore, compare and report on island health issues facing in the western Pacific, before making appropriate recommendations. A review of selected health indicators in Pacific islands was collected from the World Health Organization (WHO) and other publicly available resources. In the Pacific region, 15 islands saw lower health expenditure (<US $500), one physician and two to six nurses per 1,000 people (fall below WHO recommendation), lower life expectancy (60-70 years), higher fertility rates (2.5 to 6.4 children per women, excepting Palau), and higher adolescent fertility rates (23 to 88 children per 1,000 girls, excepting Tonga). Island populations also suffer a higher disease burden per 100,000 people, with TB, malaria, and non-communicable diseases contributing to elevated mortality rates throughout much of the region. This article highlights four areas: the sustainable development of the health workforce, improved maternal and antenatal health care provisioning, and selective communicable and non-communicable disease control. However, there are some limitations especially under reporting of maternal health data and generalization effect of reported data.